Morphometric Analysis of Foremen Magnum and Occipital Condyles Using CT Scan and its Relation to Gender (Medical Forum Monthly, 2026)
Objective: This study focuses on the morphometric features of the foramen magnum and occipital condyles to assist in surgical procedures and forensic identification, with an emphasis on their correlation with gender.Study Design: Retrospective study, analysing 3D-CT images of the skull base from 111 Pakistani individuals.Place and Duration of Study: This study was conducted at the Radiology department of M. Islam Teaching Hospital, Gujranwala from March 2024 to February 2025.Methods: Head CT scans of 111 individuals (58 males, 53 females) were analyzed using a Toshiba Aquillion 64- slice CT scanner (1 mm slice thickness, non-contrast). Measurements included foramen magnum length, width, area; right and left occipital condyle length and width; and minimum and maximum intercondylar distances. Data were analyzed using SPSS Version 23.Results: A total of 111 CT scans were analyzed. The mean foramen magnum length was 36.68 ± 3.93 mm and width 29.76 ± 3.08 mm. Length, width, and intercondylar distances showed statistically significant differences between males and females. The mean right and left occipital condyle lengths were 23.75 mm and 23.47 mm, respectively. Left condyle width averaged 11.73 mm in males and 11.69 mm in females. The mean foramen magnum area was significantly larger in males (893.77 ± 164.82 mm²) than in females (828.17 ± 158.85 mm², p < 0.05).Conclusion: Morphometric measurements of the foramen magnum and occipital condyles serve as vital anatomical landmarks that enhance the safety and precision of surgical planning in the craniovertebral region. They also provide CT-based, region-specific anatomical data for the Pakistani population and contribute to forensic identification by highlighting gender-based differences.